Relationship of Helicobacter pylori Infection with Gastric Black Spots Shown by Endoscopy - Adachi, Kyoichi (Intern Med, 2018)
OBJECTIVE: The recently reported endoscopic finding of black spots is defined as black pigmentation in gastric mucosa. We attempted to clarify the relationship between the Helicobacter pylori infection status and black spot occurrence. METHODS: The study subjects were 1,600 individuals who underwent an annual medical checkup and whose H. pylori status could be determined. Upper endoscopic examinations were performed in all, and the presence of black spots in the stomach as well as the degree of gastric mucosal atrophy were determined. RESULTS: Among the 1,600 enrolled subjects, 784 underwent eradication for H. pylori, of whom 144 were originally H. pylori-positive and 672 H. pylori-negative. Black spots in the stomach were observed in 156 (9.8%). The rate of prevalence of black spots in the H. pylori-positive and H. pylori-negative subjects was 2.1% and 1.5%, respectively, while that in subjects after undergoing eradication of H. pylori was 18.2%. A multiple logistic regression analysis demonstrated that an older age and post-eradication status were significant factors for black spot occurrence, while proton pump inhibitor treatment showed a tendency to be a risk factor. In subjects with post-eradication status, a higher grade of gastric mucosal atrophy was a significant risk factor for the occurrence of black spots. CONCLUSION: H. pylori post-eradication status and an older age were significant factors related to the appearance of black spots, and a higher grade of gastric mucosal atrophy was also a significant risk factor in subjects who had undergone successful eradication.